ANALISIS PERFORMANCE PERANCANGAN JARINGAN FIBER OPTIC PADA RSUD WANGAYA KOTA DENPASAR DENGAN OPTISYSTEM - Putra Maharddhika, I Nyoman; Putra Sastra, Nyoman; Wiharta, Dewa Made (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUM, 2022)
The hospital information system has been regulated in Law Number 44 of 2009 concerning Hospitals. The law states that every hospital is required to record and report all hospital operations in the form of a hospital management system. In this regard, the research conducted at Wangaya Regional General Hospital, Denpasar City, aims to determine the performance calculation of the fiber optic network design at the hospital so that SIMRS implementation can be carried out optimally. This research uses Optisystem 7.0 simulation to determine the performance of network design at Wangaya Regional General Hospital, Denpasar City. Optisystem simulation with MMF OM4 cable produce a power receive value greater than allowable minimum receiver sensitivity, that is -11.1 dBm. The BER value obtained from the Optisystem simulation is less than 1x10-9 which indicates that the value has met the adequacy of the standard BER value in fiber optic networks. However, the Q-factor value obtained in the simulation is greater than the optical communication standard, that is 6. This design is feasible to implement using MMF OM4 cable from the results of testing with Optisystem simulations.